In vitro biological activity of seed oil of Withania coagulans and synthesis of catalyst from residual biomass - Raghav, Priya; Sharma, Nishesh; Choudhary, Priyvart; Kumar, Nishant; Sharma, Rohit; Badoni, Himani; Chaudhary, Ayushi (Plant Science Today, 2025)
Withania coagulans is a well-known medicinal plant reported to possess numerous biological activities. However, the plant remains underutilized compared to other medicinal plants due to lack of clinical and analytical studies. In the present study, in vitro biological activities of oil extracted from seeds of W. coagulans were studied along with synthesis and characterization of catalyst from residue obtained post oil extraction. The extracted oil exhibited DPPH-radical scavenging activity, protein denaturation activity and in vitro -? amylase inhibitory activity. These activities were comparable to the corresponding activities of standard compounds indicating diverse medicinal potential of the oil. The residue obtained post oil extraction was utilized for synthesis of catalyst. The synthesized catalyst was characterized to identify the nature of the catalyst. Catalyst synthesized from residue was found to be silica-based catalyst, crystalline in nature and EDX mapping revealed catalyst to comprise of C, O, Na, Si, P and Ca. Interpretation of results obtained depict potential utilization of W. coagulans for diversified traditional as well as industrial application.